Gender inequality and female body language in children's literature. (7th December 2020) - Čermáková, Anna; Mahlberg, Michaela
Abstract: In this paper, we aim to situate corpus linguistic approaches to literary texts within the wider context of digital humanities. With an exploratory case study of gendered body language in children's literature, we illustrate the relationship between quantitative and qualitative analysis. The case study is focused on female body language descriptions and how the presentation of body language has changed over time. We work with two corpora of children's literature: 19th century and contemporary fiction. Our analysis confirms the substantial imbalance in the representation of female and male characters that has been identified by earlier studies and also shows a more nuanced picture of emerging subtle changes.